Creating a Family or Loyalty-Based Framework: The Effects of Paternalistic Leadership on Workplace Bullying - Soylu, Soydan (Journal of business ethics, 2011)
Prior research has demonstrated that issues in leadership problems can lead to both negative organisational outcomes and unethical practices at work, such as bullying and counterproductive behaviours. This study investigates the association of bullying with paternalistic leadership dimensions (i.e. creating family atmosphere at work, maintaining individualised relationships, non-work involvement, loyalty seeking and maintaining authority). Seven hundred and fifteen questionnaires were collected from employees in Turkish workplaces. Confirmatory factor analyses were used to examine the bullying phenomenon and paternalistic leadership with respect to their dimensions. Hierarchical regression analyses revealed that ‘expecting loyalty in exchange for nurture at work’ relates positively with the experience of bullying. In contrast, findings indicated a negative association between leadership involving ‘behaving like a senior family member at work’ and bullying. Plausible explanations of the findings were discussed by referring to relevant ethical climate literature.